The effectiveness of essential oil from Citrus limon peel on Candida albicans biofilm formation: An experimental in vivo study - Desiana Radithia, PhD; Rindang Tanjungsari, DDS; Diah Savitri Ernawati, Professor; Adiastuti Endah Parmadiati, MDS (Journal of Taibah University Medical Sciences, 2023)
الملخص: أهداف البحث: تظهر ''المبيضات البيضاء'' مقاومة للأدوية المضادة للفطريات. لذلك، من الضروري استخدام المواد المشتقة من المصادر الطبيعية كعامل مضاد للفطريات. يظهر الزيت العطري من قشر الليمون الحمضي قدرة على منع نمو المبيضات البيضاء في المختبر. الغرض من هذه الدراسة هو تحديد مستوى التركيز الأكثر فعالية للزيت العطري من قشر الليمون الحمضي في تثبيط التغيرات الشكلية الخلوية للمبيضات البيضاء وتشكيل الأغشية الحيوية في الجسم الحي. طرق البحث: تم حقن ذكور فئران ويستار يتراوح وزنها بين 200 و 300 جرام بالمبيضات البيضاء لمدة 48 ساعة ثم أعطيت جرعة واحدة من ميثيل بريدنيزولون عن طريق الفم كمثبط للمناعة. تم وضع زيت عطري من قشر الليمون الحمضي في شكل هلام وبثلاث تركيزات مختلفة (0.39٪ ، 0.78٪ و 1.56٪) مرتين في اليوم لمدة يومين. تم التضحية بالجرذان بعد 48 ساعة ثم تم تحضير أنسجة الغشاء المخاطي الحنكي لفحصها باستخدام المجهر الإلكتروني الماسح للكشف عن التغيرات الشكلية الخلوية وتشكيل الأغشية الحيوية للمبيضات البيضاء. النتائج: أظهر الزيت العطري من قشر الليمون الحمضي تركيز 1.56٪، بالمقارنة مع 0.78٪ و 0.39٪، أقوى قدرة على تثبيط تكون المبيضات البيضاء. عطل الزيت العطري من قشر الليمون الحمضي حصول التغيرات الشكلية الخلوية. تم عرض الخلايا التي لم تكن سليمة أو مستعمرة، وظهرت الشعيرات حول الخلايا ناعمة، واختفت طبقة الأغشية الحيوية، ولم يحدث تكوين خيطان. الاستنتاجات: تأثير الزيت العطري من قشر الليمون الحمضي على التغيرات الشكلية الخلوية وتكوين الأغشية الحيوية يتأثر بتركيزه، وأظهر الزيت العطري من قشر الليمون الحمضي بنسبة 1.56٪ أقوى قدرة على تثبيط التغيرات الشكلية الخلوية وتكوين الأغشية الحيوية. تسلط هذه النتائج الضوء على الزيت العطري لقشر الليمون الحمضي كمرشح مضاد للفطريات لعلاج داء المبيضات. Abstract: Objectives: Candida albicans is resistant to commercial antifungal agents. Therefore, it is desirable to use material derived from natural sources as an antifungal agent. Essential oil from Citrus limon peel is able to inhibit the growth of C. albicans in vitro. The purpose of this study was to determine the most effective concentration of essential oil from C. limon peel with regards to the inhibition of C. albicans cyto-morphometric changes and biofilm formation in vivo. Methods: Male Wistar rats weighing 200–300 g were inoculated with C. albicans for 48 h and then given a single dose of oral methylprednisolone as an immunosuppressant. Essential oil from C. limon peel, in a gel form and at three different concentrations (0.39%, 0.78% and 1.56%), was applied twice a day for 2 days. The rats were killed after 48 h and then palatal mucosa tissues were prepared and examined with a scanning electron microscope (SEM) with regards to C. albicans, cyto-morphometric changes and biofilm formation. Results: Essential oil from C. limon peel at a concentration of 1.56% showed the strongest ability to inhibit C. albicans growth when compared to 0.78% and 0.39%. At a concentration of 1.56%, essential oil from C. limon peel disrupted cyto-morphometric changes; cells that were neither in intact nor colonised were evident, the filaments around the cells were smooth, the layer of biofilm had disappeared and there was no evidence of hyphae formation. Conclusion: The effect of essential oil from C. limon peel on cyto-morphometric changes and biofilm formation was concentration-dependent. Essential oil from C. limon peel at a dose of 1.56% showed the strongest ability to inhibit cyto-morphometric changes and biofilm formation. These findings demonstrate that essential oil of C. limon peel is a potential antifungal candidate for the treatment of candidiasis.